Cache-skip approach for information-centric network - Abdullahi, Ibrahim; Che Mohamed Arif, Ahmad Suki (Asian Research Publishing Network (ARPN), 2016)
Several ICN cache deployment and management techniques have since been using the Web management techniques to manage information sharing and better cache-hit ratio.Leave Copy Down, Leave Copy Everywhere and Probabilistic cache managements have gained more attention. However, with Leave Copy Everywhere being the initial design specification in ICN proposal, several research issues of content manageability have posed a threat of particularly content and path redundancy.This paper presents an extensive simulation analysis of the popular cache management techniques by subjecting the concepts into different network topologies to investigate the prospect of extending and proposing a new form of cache management in ICN known as Cache-skip. Cache-skip use the consciousness of time of request, network size and Time Since Birth (TSB) and Time Since Inception (TSI) to carefully dedicate the positions of caching to benefits hit rates and less network stress as a form to efficiently utilize the bandwidth and enhance hits.